Extending the Extensional Lambda Calculus with Surjective Pairing is Conservative - Støvring, Kristian (BRICS Report Series, 2006)
We answer Klop and de Vrijer’s question whether adding surjective-pairing axioms to the extensional lambda calculus yields a conservative extension. The answer is positive. As a byproduct we obtain the first ``syntactic’’ proof that the extensional lambda calculus with surjective pairing is consistent.